2017
DOI: 10.1097/meg.0000000000000806
|View full text |Cite
|
Sign up to set email alerts
|

Performance characterization of a novel electronic number connection test to detect minimal hepatic encephalopathy in cirrhotic patients

Abstract: The novel eNCT is a reliable HE self-test to monitor cognitive function and detect cognitive impairment in cirrhotic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
0
12
0
1
Order By: Relevance
“…Wuensch et al found that the eNCT performance was negatively correlated with PHES performance in patients with cirrhosis. Control participants showed significantly faster eNCT completion times compared with cirrhosis patients (Wuensch et al 2017 ).…”
Section: Diagnosis Of Mhe: Cognitive Evaluationmentioning
confidence: 99%
“…Wuensch et al found that the eNCT performance was negatively correlated with PHES performance in patients with cirrhosis. Control participants showed significantly faster eNCT completion times compared with cirrhosis patients (Wuensch et al 2017 ).…”
Section: Diagnosis Of Mhe: Cognitive Evaluationmentioning
confidence: 99%
“…This study indicated that the computerized Stroop test is suitable for MHE screening in children. Moreover, Wuensch et al[ 55 ], who was inspired by the paper-pencil number connection test version A, developed a novel electronic number connection test. The electronic number connection test exhibited high sensitivity (> 82%) and high specificity (> 85%) in MHE detection with excellent test–retest reliability.…”
Section: Other Modalitiesmentioning
confidence: 99%
“…Apart from PHES, a newly developed electronic number connection test (eNCT) was investigated by Wuensh et al . 87 . This test flashes the numbers 1–25 on a screen and requires the participant to click them in order while being timed; those patients with HE were found to be much slower 87 .…”
Section: Recent Advances In the Diagnosis Of Hepatic Encephalopathymentioning
confidence: 99%
“… 87 . This test flashes the numbers 1–25 on a screen and requires the participant to click them in order while being timed; those patients with HE were found to be much slower 87 . This test promises to be an easier and faster method than PHES 87 .…”
Section: Recent Advances In the Diagnosis Of Hepatic Encephalopathymentioning
confidence: 99%